The rise and fall of the duty of suitability in the Peruvian Consumer Protection law - Rodríguez García, Gustavo (2014)
The term "suitability" is understood as the correspondence between what a consumer expects and what he actually receives. In that sense, to clarify what is meant by "duty of suitability" it is necessary to analyze theconcept of "consumer” as well.However, when it comes to our consumer protection system, can we say it is protecting the reasonable consumer, the average consumer or the negligent consumer? In this regard, what are the implications of opting for the protection of one or the  other?  In this article, the author seeks to answer these questions through an analysis of national jurisprudence regarding consumer protection.